Sensitivity of the West African hydrological cycle in ORCHIDEE to infiltration processes - T. d'Orgeval; J. Polcher; P. de Rosnay (Hydrology and Earth System Sciences, 2008)
The aim of this article is to test the sensitivity of the West African hydrological cycle to infiltration processes and to river reinfiltration pathways. This is done through sensitivity experiments to both inputs and paramterization settings of the ORCHIDEE Land-Surface Model. The parameterizations to take into account the effects of flat areas, ponds and floodplains on surface infiltration, and the effect of roots and deep-soil compactness on infiltration are first described. The sensitivity analysis to parameterization settings shows that the surface infiltration processes have a stronger impact in the soudano-sahelian region and more generally in semi-arid African regions, whereas the rootzone and deep-soil infiltration also play a role in the guinean and intermediate regions between arid and humid ones. In the equatorial and semi-humid regions, infiltration processes generally play a minor role. The infiltration parameterizations may explain part of the difference between simulated and observed river discharge in semi-arid and intermediate basins. The sensitivity analysis to the Land-Surface Model inputs shows that different sources of uncertainty might also explain part of the error. Indeed, the precipitation forcing in the whole West African region, the long-term storage in the soudano-sahelian region, the soil types in the guinean region and the vegetation types in the equatorial region are significant sources of errors. Therefore, observations and analyses of small scale infiltration processes as well as continuous measurements of river discharges in West Africa are essential to ensure the reliability of future calibration for the infiltration parameterizations.